1958
DOI: 10.6028/jres.060.005
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of polyamides

Abstract: Thermal decomposition s of various nylon samples havin g difTcrenL molec ular weights and composition were investigated by several procedures: ( I ) Th e raLc of volaLiliulLion at temperatures between 310 0 and 380 0 C; (2) t he analysis of the volatile produets by mass spectrometry; and (3) a direct m eas urement of volaLili zing m aterial obtained by eHtTying out the pyrolysis within the ionization chamber of a m ass spectromeLer.AcLivation energies based on the rates of volatilization for the variolls ample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1958
1958
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(39 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…When linear samples of polymethylene made from diazomethane are pyrolyzed, maximum-type curves are produced [15]. Commercial linear polyethylene and polyamides also give rate curves with maxima very similar to that for random theory [11].…”
Section: 3 Rates Of Volatilizationmentioning
confidence: 95%
“…When linear samples of polymethylene made from diazomethane are pyrolyzed, maximum-type curves are produced [15]. Commercial linear polyethylene and polyamides also give rate curves with maxima very similar to that for random theory [11].…”
Section: 3 Rates Of Volatilizationmentioning
confidence: 95%
“…Straus and Wall [21,25], investigated the decomposition of nylon mixtures by experiments on the ra a of volatilization. They concluded that the decomposition is a thermal free-radical decomposition complicated by the residual polymerization catalysts and water strongly bonded to the peptide links.…”
Section: Nylonmentioning
confidence: 99%
“…The presence of cyclopentanone in the degradation products of poly(di-n-butyltin adipate) as well as in poly-(hexamethylene adipamide) supports the view that this material originates from the adipic acid rather than the hexamethylene diamine moiety of nylons 66. 3 Only trace amounts of carbon monoxide were found in both samples of organotin polyesters in contrast to the situation with other polyesters, including poly(ethy1ene terephthalate), where both carbon monoxide and carbon dioxide are produced in larger and about equal amount^.^ Butane most likely originates from the cleavage of the butyl side groups of both organotin polyesters. Carbon dioxide arises from the scission of the carboxyl links, except in the case of poly(di-n-butyltin adipate), where one of the carboxyl groups of the repeat unit participates in the formation of cyclopentanone.…”
mentioning
confidence: 72%